Atomic Scale Structure Inspired 3D‐Printed Porous Structures with Tunable Mechanical Response. Issue 7 (17th April 2021) - Ambekar, Rushikesh S.; Mohanty, Ipsita; Kishore, Sharan; Das, Rakesh; Pal, Varinder; Kushwaha, Brijesh; Roy, Ajit K.; Kumar Kar, Sujoy; Tiwary, Chandra S.
Abstract : To enhance the overall energy efficiency of the individual parts used in automobile and aerospace industries, study of the specific strength of the components becomes crucial. As a result, in the last couple of decades, large efforts have been made to develop porous architecture with light weight and high specific strength. Herein, an easily scalable and controlled processing of a stochastic bicontinuous atomic scale structure inspired complex porous architecture using 3D printing is demonstrated. The complex topology of the architecture provides enhanced mechanical properties (specific strength, modulus, specific energy absorption etc.). These properties can be easily tuned with the help of changing density and surface area. Based on experimental observations, an analytical model is proposed to correlate these properties with density. These individual architectures can be stacked on top of each other with different combinations to build hierarchical structures, which allows engineering of the directional dependency of the mechanical response. Abstract : An atomic scale structure inspired porous architecture is developed via 3D printing technique. The effect of the density, topology and surface area on mechanical properties e.g. young's modulus and specific energy absorption are studied. Gibson‐Ashby foam scaling law is incorporated into study and stress distribution is analysed. The direction‐dependent mechanical response of the hierarchical structures is discussed.